Urethrocystoscopic-guided scissor correction of vestibular vaginal changes as minimally invasive treatment option to endoscopic scissors in female dogs: 13 cases (2022-2024). - Martinelli, Carolina; Colatto, Jiuliany Breda; Silotti, Juliano Jácomo Mendes; Galimberti, Pietra Da Silva; Ferreira, Juarez Henrique; Senhorello, Igor Luiz Salardani [UNESP]; Raposo-Ferreira, Talita Mariana Morata (American Veterinary Medical Association (AVMA), 2025)
Objective: To evaluate the incidence and effectiveness of urethrocystoscopy-guided scissor correction for vestibulovaginal anomalies in female dogs. Methods: The study included 13 female dogs treated between September 2022 and September 2024 at the Veterinary Nephrology and Urology Center. Diagnosed anomalies were persistent paramesonephric septal remnants (10 cases), vaginal septa (2 cases), and double vagina (1 case). Inclusion criteria were clinical signs of urinary tract infections and anomalies confirmed via endoscopy. Urethrocystoscopy-guided scissor correction was performed. Preoperative assessments included bloodwork, urinalysis, urine culture, sensitivity testing, and ultrasonography. Outcomes were monitored for 1 year postprocedure. Results: Persistent paramesonephric septal remnants were the most common (10 cases). Associated conditions included ectopic ureters (4 cases), bladder wall thickening (4 cases), and urolithiasis (7 cases). Mean correction time ranged from 30 to 93 minutes, depending on the anomaly. Clinical signs such as dysuria, pollakiuria, hematuria, and urinary incontinence resolved in most cases. Minor complications included transient intraoperative bleeding that did not require discontinuation. Conclusions: Urethrocystoscopy-guided scissor correction proved effective and minimally invasive for treating vestibulovaginal anomalies, with high success rates and minimal morbidity. Clinical signs resolved in most cases, supporting its use as an alternative to traditional surgery or laser ablation. Clinical Relevance: This technique offers a safe, cost-effective option for treating vestibulovaginal anomalies in dogs, improving clinical outcomes, and reducing complications. Further studies with larger sample sizes are recommended to validate these findings.